A comparative research on teachers’ knowledge in five Asia-Pacific countries in the COVID-19 pandemic: The case of tourism and hospitality education - Chen, Yen-Jung; Hsu, Liwei (Frontiers in Education, 2022)
The COVID-19 outbreak at the beginning of 2020 has drastically impacted almost every aspect of our daily life. Empirical evidence is lacking on which sector of knowledge in technology-enhanced teaching needs to be developed further for tourism and hospitality programmes conducted online. The present study investigated teachers’ technology, learners, pedagogy, academic discipline content knowledge, and context knowledge (TLPACK) in tourism and hospitality online education settings using comparative research methods. One hundred and seventy-three participants from five countries (Indonesia, Philippines, Taiwan, Thailand, and Vietnam) were surveyed online. The results revealed that all teachers reached a consensus that their knowledge about learners was the lowest during the online teaching period of the pandemic. Additionally, their TLPACK revealed significant differences in various countries. This study overcomes a major limitation of previous studies on how the pandemic has affected educational praxis as the focus of previous research has been on the situation in a single country. Therefore, the present study’s findings can serve as a reference for practitioners of tourism and hospitality online education in Asia Pacific region when facing unprecedented and urgent changes of educational practices during and post the COVID-19 pandemic.